DARKER BY FOUR - Tan, June CL (New York, NY : HarperTeen, an imprint of HarperCollins Publishers, 2024)
ui has one goal in mind, honing her magic to avenge her mother's death. Yiran is the black sheep of an illustrious family. The world would be at his feet, had he been born with magic. Nikai is a Reaper, serving the Fourth King of Hell. When his master disappears, the underworld begins to crumble, and the human world will be next if the King is not found. When an accident causes Rui's power to transfer to Yiran, everything turns upside down. Without her magic, Rui has no tool for vengeance. With it, Yiran finally feels like he belongs. That is, until Rui discovers she might hold the key to the missing death god and strikes a dangerous bargain with another King. As darkness takes over, three paths intersect in the shadows. And three lives bound by fate must rise against destiny before the barrier between worlds falls and all Hell breaks loose, literally
Keywords: Revenge -- Fiction; Magic -- Fiction; Young adult fiction; Fantasy fiction; Paranormal fiction